FLEXIBLE WORKING ARRANGEMENT ON JOB PERFORMANCE MEDIATED BY WORK-LIFE BALANCE AMONG EMPLOYEES - Az-Zahra, Chairunnisa; Purwana, Dedi; Suherdi (Faculty of Economics and Business, Universitas Negeri Jakarta, 2024)
This research aims to determine whether or not there is a direct and indirect influence of flexible work arrangements on work-life balance and employee performance. A causality descriptive quantitative research design was used for this research. Employees of PT. Andalan Utama Foodindo are the population and sample of this research, with a total of 54 respondents using census techniques. Data were analyzed using path analysis using the SPSS program. The study's findings show that the variables have a positive relationship: a flexible work schedule has a regression coefficient of +0.310 on job performance. Additionally, work-life balance influences job performance with a regression coefficient of +0.626, and flexible working arrangements influence work-life balance with a regression coefficient of +0.647. Furthermore, with a mediation effect of 4.505, the research findings show that work-life balance acts as a mediating variable in the association between flexible working arrangements and job performance.